THE ROLE OF PAREMIA IN THE SYSTEM OF NATIONAL CULTURAL HERITAGE. - Mirzaeva, Dilshoda (Журнал иностранных языков и лингвистики, 2021)
In this article, I try to analyze the linguoculturological aspects of English and Uzbek parems, to describe the interdependence of language and culture, to consider thematically similar aspects of English and Uzbek paremies and to express their national character.